Analisis Tindak Tutur Interaksi Sosial Masyarakat Pasar Gempol - Nur Ilmilah; Roni Nugraha Syafroni; Suntoko Suntoko (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to describe the types of speech acts, to find out the functions of speech acts. The method used in this research is descriptive method. The form of this research is qualitative. Data collection techniques used are listening techniques, recording techniques, and note-taking techniques. The data collection technique was used to obtain complete data. Based on the findings from the research data analysis stage, it was found 10 selected data from sellers or buyers in the Gempol market area with data details as follows. Locutionary use of speech acts was 84 times, which functioned as commissive pragmatics 16 times, assertive pragmatics 49 times, directive pragmatics 11 times, expressive pragmatics 8 times. Then this research is used as teaching materials for negotiating texts to facilitate the learning process.